Ion-imprinted electrospun nanofibers of chitosan/1-butyl-3-methylimidazolium tetrafluoroborate for the dynamic expulsion of thorium (IV) ions from mimicked effluents - Gore P.M.; Khurana L.; Siddique S.; Panicker A.; Kandasubramanian B. (My University, 2025)
The present study explores the innocuous, biocompatible, and extremely competent molecularly imprinted chitosan/RTIL electrospun nanofibers having average diameter of 30 nm for the expulsion of thorium (IV) ions from the mimicked effluent waste. The extended Flory–Huggins theory and three-dimensional molecular modeling have been effectively premeditated via Materials Studio software for enumerating the inter-miscibility and compatibility (Chi parameter (χ) = 1.019, mixing energy (Emix) = 0.603 kcal/mol) of the chitosan/RTIL (1-butyl-3-methylimidazolium tetrafluoroborate). The maximum adsorption efficiency is found to be 90% at a neutral pH of 7, and a temperature of 298 K within 120 min. The adsorption process was extensively studied by two-parameter adsorption isotherms like Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich (D–R) and three-parameter models like Redlich–Paterson and Sips isotherm. Pseudo-second-order kinetics model (R2 = 0.982) and Langmuir isotherm (R2 = 0.994) bestowed the best fitting on chitosan/RTIL nanofibers for the adsorption of Th (IV) ions. The thermodynamic study reveals the spontaneity and exothermic nature of the reaction. The experimental analysis conjoint with isotherm and kinetic models, and simulation study establish the applicability of chitosan/RTIL nanofibers for the expulsion of Th (IV) and other toxic metal ions from the effluents. [Figure not available: see fulltext.]. © 2017, Springer-Verlag GmbH Germany.